Biblical Archaeology : A Very Short Introduction - Cline, Eric H. (New York Oxford University Press, 2009)
"Archaeologist Cline discusses the origins of biblical archaeology as a discipline and what first prompted explorers to go in search of sites that would 'prove' the Bible. He surveys some of the sites, including Hazor, Megiddo, Gezer, Lachish, Masada, and Jerusalem. Separate chapters deal with the Hebrew Bible and New Testament, frauds and forgeries, and future prospects"--Provided by publisher.
Include Illustrations and Index
Keywords: Bible -- Antiquities. -- Antiquities & Archaeology. -- RELIGION